2015
DOI: 10.1111/cura.12137
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Visitor Experience at Immersive and Tabletop Exhibits

Abstract: Many museum professionals believe that immersive exhibits—those that surround visitors—provide more attractive, engaging and effective learning experiences than tabletop exhibits. We investigated this claim by comparing visitors’ experiences of the two exhibit types, using pairs of exhibits that differed in scale (immersive vs. tabletop), but shared the same content and similar visitor activity. We randomly selected, videotaped, interviewed, and sent follow‐up surveys to sixty families who experienced immersiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 30 publications
2
20
0
Order By: Relevance
“…Eight groups used the opportunity to collect photos. The findings match findings from Dancstep et al (2015) that whole-body interactive exhibits have a diminished intellectual engagement compared to hands-on exhibits that also held the visitors' attention for a longer period. The family groups did not discuss the exhibit themes more often or more comprehensively compared to the school groups, contrary to findings by Crowley et al (2001).…”
Section: Becoming (Too) Immersedsupporting
confidence: 82%
See 2 more Smart Citations
“…Eight groups used the opportunity to collect photos. The findings match findings from Dancstep et al (2015) that whole-body interactive exhibits have a diminished intellectual engagement compared to hands-on exhibits that also held the visitors' attention for a longer period. The family groups did not discuss the exhibit themes more often or more comprehensively compared to the school groups, contrary to findings by Crowley et al (2001).…”
Section: Becoming (Too) Immersedsupporting
confidence: 82%
“…As such, the findings support the general believe that immersive, whole-body experience may be capable of enhancing visitor learning (Wellington, 1998;Gilbert, 2002). As in Dancstep et al (2015), only few visitors expressed their reasoning verbally, but they showed their sensemaking when trying to improve their jumping techniques. Yet again, these findings demonstrate the importance of a conceptually coherent exhibit design with clear connection between lines of reasoning, for example, you can jump higher if you combine coordination and muscle strength (Allen 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Return Visits: We posit that return visits are also indicative of engagement, though used less commonly (Dancstep et al. ). Similar to other indictors of engagement in situations where learners are free to choose, we believe returning to use an exhibit again suggests higher interest and engagement (Diamond ; Falk ; Humphrey and Gutwill ; Sandifer ; Serrell ; Yalowitz and Bronnenkant ).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies of exhibit designs have ranged from single exhibits to exhibition collections of 30–60 exhibits, and typically focus on only a handful of design attributes (see for example, Borun and Dritsas ; Dancstep et al. ; Gutwill‐Wise and Allen ; Perry ; Sandifer ; Sanford ). The large number of design attributes identified in the FRD Framework necessitated a much broader investigation.…”
Section: Current Studymentioning
confidence: 99%